Peripheral arterial pathology and osteoarthritis of the knee: US examination of arterial wall stiffness, thickness, and flow characteristics - Jon Olansen; Minglang Yin; Janine Molino; Thomas Carruthers; Derek Jenkins; George Karniadakis; Roy K. Aaron (Osteoarthritis and Cartilage Open)
Background: Osteoarthritis (OA) is a widespread chronic joint disorder characterized by the degeneration of articular cartilage, extensive bone remodeling, ligamentous fibrosis, and synovial inflammation impacting millions. Shared factors like phenotypic similarities, hypofibrinolysis, and inflammation constitute similarities in pathophysiology and clinical manifestations between OA and peripheral vascular disease (PVD). This study investigated peripheral arterial flow characteristics, vascular wall thickness, and stiffness in knee OA to clarify a potential association with early atherosclerosis. Methods: The OA cohort consisted of 35 knees with a mean age of 69 years. The control cohort consisted of 58 knees with a mean age of 68 years. Subjects underwent arterial ultrasound scanning of the common femoral, superficial femoral, and popliteal arteries. Data measured included peak systolic volumetric flow, intima-media thickness, systolic and diastolic vessel diameter, and simultaneous EKG and flow curves. Structural and functional vascular data were quantified using the incremental Young's modulus, pulse wave velocity (PWV), and distensibility. Results: Significantly elevated arterial volumetric flow, measures of arterial stiffness, and intima-media wall thickness were observed in those with OA compared to those without. PWV as calculated by the Bramwell-Hill equation were found to be significantly greater in all three vessels of patients with OA. Conclusions: This study supports the association between peripheral arterial pathology and knee OA, consistent with shared clinical and phenotypic traits. The observed characteristics of early vascular pathology suggest potential pathophysiologic linkages between OA and PVD. This foundational framework provides avenues for mechanistic studies exploring the relationship between these two disease processes.